Screening and validation of key genes involved in castration-resistant prostate cancer based on transcriptomics sequencing - Guangquan Tong; Xiaomeng Jing; Yuning Yang; Xiaowei Wang; Junlin Lu; Jingyi Hu; Yang Wang; Farra Aidah Jumuddin; Wenjing Zhang; Yuesheng Lv (Scientific Reports)
Abstract Prostate cancer is one of the most common malignant tumors occurring in the male reproductive system. Androgen deprivation therapy (ADT) is the primary treatment for prostate cancer. However, approximately 10–20% of advanced prostate cancer patients progress to castration-resistant prostate cancer (CRPC) within five years, posing a significant challenge to treatment. There is an urgent need to explore the causes and mechanisms of prostate cancer progression, and to identify new therapeutic targets and predictive markers. Utilize RNA-seq to screen for differentially expressed genes and alternative splicing events between androgen-sensitive prostate cancer cells and castration-resistant prostate cancer cells. Perform bioinformatics analysis on the differentially expressed genes. The expression levels of these genes were confirmed by real-time quantitative PCR (RT-qPCR); alternative splicing events related to castration resistance were verified through RT-PCR. The impact of the S100A6 gene on the proliferation and growth capabilities of PC3 and DU145 cells was analyzed using CCK8, colony formation, and EdU assays. Cell migration was assessed using a wound healing assay. The RNA-seq analysis results showed that there were 4,830 differentially expressed genes in non-hormone-sensitive prostate cancer. GO enrichment analysis of these differentially expressed genes revealed significant enrichment in tumor-related signaling pathways such as regulation of cell cycle process, cell division, and regulation of cell projection organization. Further RT-qPCR detection results indicated that the mRNA expression of four genes, including S100A6, was upregulated, consistent with the transcriptome sequencing results. Downregulation of S100A6 expression significantly inhibited the proliferation and migration of non-hormone-dependent prostate cancer. In this study, we also identified many splicing alterations in cancer-related genes, with castration resistance-induced alternative splicing events closely related to the interaction networks of regulation of cell cycle process, cell division, and regulation of cell projection organization. Our research findings suggest that S100A6 may serve as a molecular marker or therapeutic target associated with castration resistance in prostate cancer, providing new insights into the molecular basis of this disease.